Determination of metal contents in various chocolate samples - Alagić, Nerma; Huremović, Jasna (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2015)
Seven metals (Mn, Cu, Zn, Cd, Cr, Fe, and Pb) were determined in 17 different samples of chocolate and commonly consumed cocoa products using atomic absorption spectrometry, flame technique (F-AAS). Samples were prepared by wet digestion with concentrated nitric acid. Concentrations of metals (Mn, Fe, Cu and Zn), with exception of Cr, Pb and Cd, were found to be the highest in cocoa powder and black chocolate with a high content of cocoa. Concentrations of Cu, Cd and Pb were found to be below permissible levels prescribed by national Regulation of maximum permitted quantities of certain contaminants in food B&H in all samples.